Role of Product Packaging in Market Strategy: A Case Study of Nepalese Organization - Khand, Riya Rajyalaxmi (Nepalese Journal of Management, 2024)
This study examines the role of product packaging in market strategy of Nepalese organization. The dependent variable is marketing strategy. The selected independent variables are, innovativeness, security and privacy, perceived trust, brand perception, and brand communication. The primary source of data is used to assess the opinions of respondents regarding innovativeness, security and privacy, perceived trust, brand perception, and brand communication. The study is based on primary data of 112 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of role of product packaging in market strategy: A case study of Nepalese organization. The study showed a positive impact of innovativeness on marketing strategy. It indicates that innovative product packaging helps to develop customer oriented marketing strategy. Similarly, the study showed a positive impact of security and privacy on marketing strategy. It indicates that more secure packaging, better would be the marketing strategy of the company. Likewise, the study also revealed a positive impact of perceives trust on marketing strategy. It indicates that higher the level of perceived trust on product packaging, better would be the marketing strategy of the company. Further, the study observed a positive impact of brand perception on marketing strategy. It indicates that higher the level of brand perception of the customers towards packaging, better would be the marketing strategy. In addition, the study observed a positive impact of brand communication on marketing strategy. It indicates that higher the brand communication about packaging helps to develop customer oriented marketing strategy.